Principles and Practice of Islamic Leadership - Abdul Mutalib, Mahazan; Rafiki, Ahmad; Wan Razali, Wan Mohd Fazrul Azdi. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book elaborates the fundamental principles and practices of Islamic leadership and management by highlighting its underlying philosophies, key concepts, and sources. The book closely examines the relationship of Islamic leadership with spiritual leadership and how it shapes the concept of leadership. The book also compares Islamic Leadership with other related spiritual leadership concepts such as the Servant Leadership, religiosity, and other conventional leadership perspectives based on Islamic framework. The chapters within the book delve into Islamic teachings and values from Al-Qur'an and Hadith that can be applied when governing an organization using several case studies. This insightful and thorough discussion on Islamic leadership will be useful as a reference for academic courses on leadership, and current and aspiring business leaders.
Chapter 1. Introduction -- Chapter 2. The Moral Based of Islamic Leadership -- Chapter 3. The Characteristics and the Traits of Leadership -- Chapter 4. Spirituality and Servant Leadership -- Chapter 5. Qalb Leadership process -- Chapter 6. Al-Ghazali and the Four Cardinal Virtues -- Chapter 7. Islamic Principles and Values in Organization -- Chapter 8. Conclusion.
Keywords: Strategic planning; Leadership; Management; Islam-Study and teaching; Psychology, Industrial; Business Strategy and Leadership; Management; Islamic Studies; Work and Organizational Psychology